GAMBARAN PENGETAHUAN DAN SIKAP DENGAN POSISI TAWAR KONSUMEN TENTANG PENGGUNAAN KEMASAN STYROFOAM SEBAGAI WADAH MAKANAN DI AMALIUN FOODCOURT TAHUN 2015 - Putri Ramadhani S; Fitri Ardiani; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Styrofoam packaging material was often used by traders and consumers as food packaging. It is a practical, inexpensive, pleasing to the eye and no leaking, make consumers forget the impact the dangers of Styrofoam packaging containing residues of styrene monomer that can act on greasy foods especially in hot conditions. Consumers can do the bargaining position of the Styrofoam packaging, by requiring exchange Styrofoam packaging with other packaging safer. The purpose of these study was to determine the description of the knowledge and attitude of consumers to act bargaining position when receiving packaging Styrofoam as food packaging. The research type was descriptive with cross sectional design which illustrate the knowledge and attitudes with the bargaining position of consumers on the use of Styrofoam as food packaging in Amaliun Foodcourt. This study population is consumers who buy food using styrofoam. The results of research showed that 65,0% and 82,5% of consumers have a good knowledge and attitudes about Styrofoam packaging, while consumers bargaining position of 12,5% good category. According to the level of knowledge and attitudes of consumers to the bargaining position 7,7% and 15,2% of consumers have a better bargaining position. The reason consumers do not make them lazy bargaining position to ask the exchange and traders did not have other types of packaging. Knowledge and attitudes of consumers not applied to the bargaining position of the Styrofoam packaging, to take preventive authors suggest to the Drug and Food Control Agency (BPOM) field should improve surveillance of food packaging that is circulating in the community. Key words: Bergaining Position, Styrofoam, Knowledge, Attitude, Consumer